The impact of transformational leadership on the job satisfaction of internal employees and outsourced workers - Raquel Escortell; Asier Baquero; Beatriz Delgado (Cogent Business & Management, 2020)
Transformational leadership has become a successful management tool for managers in the hotel industry. The primary aim of this study is to investigate the relationship between leadership and job satisfaction, as well as any differences between internal employees and outsourced workers. A novel method was adopted using fuzzy-set qualitative comparative analysis (fsQCA). A questionnaire-based survey was conducted to collect responses from 60 members of staff at four- and five-star hotels in Spain. Across the sample, a high level of leadership in three of the four dimensions of transformational leadership was observed to be sufficient to increase job satisfaction. The three optimal combinations of dimensions are: individualized consideration, intellectual stimulation, and idealized influence; individualized consideration, inspirational motivation, and idealized influence; and intellectual stimulation, inspirational motivation, and idealized influence. The findings suggest that there are differences between outsourced workers and internal employees. Outsourced workers need all four dimensions to achieve high job satisfaction, whereas internal employees can achieve high job satisfaction without individualized consideration.
Keywords: 650; transformational leadership; job satisfaction; fsQCA; outsourcing; hotels; tourism